Cytokines and appetite-regulating hormones in human milk and associations with infant growth across four sites in a longitudinal cohort: The Mothers, Infants and Lactation Quality Study - Sophie Hilario Christensen; Jack Ivor Lewis; Hanne Frøkiær; Peter Riber Johnsen; Janet M. Peerson; Xiuping Tan; Setareh Shahab-Ferdows; Daniela Hampel; Munirul Islam; Gilberto Kac; Daniela de Barros Mucci; Amanda C. Cunha Figueiredo; et al. (PLoS ONE, 2025)
Introduction In resource-poor settings, mother-infant dyads are commonly exposed to environmental factors increasing the risk of infectious diseases and possibly influencing the cytokine profile of human milk (HM). Hormones in HM have been proposed to influence appetite-regulation and possibly growth in exclusively breastfed infants. Objective To compare cytokines and appetite-regulating hormone (ARH) concentrations in HM of mothers from four contrasting populations and investigate associations with infant growth. Method HM samples from 825 mothers participating in the Mothers, Infants and Lactation Quality Study from Bangladesh (BD), Brazil (BR), Denmark (DK) and The Gambia (GM) were collected between 1–3.5 months postpartum and analysed for tumour-necrosis factor-α, interferon (IFN)-γ, interleukin (IL)-1β, IL-4, IL-6, IL-8, IL-10, IL-33, and insulin, leptin and adiponectin. Infant growth was measured twice between 1–5.99 months postpartum. Analysis of covariance was used to compare geometric means of HM markers between the four sites and associations between HM markers and infant growth were investigated using linear regression analysis. Results Differences in geometric means of all HM cytokines and ARHs were found among the four study sites after adjustment for possible explanatory variables. Lowest levels of most HM cytokines were found in BD, whereas highest levels of IFN-γ, IL-4, IL-10 and IL-33 were found in DK. In GM, cytokines and ARHs were inversely associated with weight-for-age and weight-for-length Z-scores. Conclusion We showed significant differences in HM composition of cytokines and ARHs among the four countries. Highest levels of T helper cell type 2 cytokines, which is typically related to increased risk of atopic diseases, were found in DK. The results may reflect the influence of different environmental exposures in the four sites on HM composition, which may be associated with infant growth in GM.